Input energy requirements for processing convenient chicken products - Sachdevl, A. K.; Ram Gopal,; Rajvir Singh, (Universiti Putra Malaysia Press, 2003)
In order to assess the economic Production of cooked chicken stock and cooked gizzard stock, data were collected on Product yield, input output energy requirements and qualitative differences in these Products Processed manually at experimental scale. A total of eight trials, including four replicates, were done for each Product. Preparation of cooked chicken stock rendered 46.24% and 69.01 % yield for raw and de-skinned chicken meat respectively, whereas the Processing ofcooked gizzard stock yielded 36.79% and 60.05%Product for raw and defatted gizzard respectively. Pilot studies on input energy requirements revealed the need for 0.765 MJ human energy (hE) and 2.617 MJ electrical inputs for Processing a kilogram (kg) of dressed chicken; while 1.138 MJ human energy and 3.148 MJ electrical inputs were required to Process a kg of raw gizzards. Physico-chemical analysis of samples showed greater shear Press value for cooked gizzard stock but overall acceptability of Products was insignificantly (P<0.05) different. However, more caloric outputs were calculated from cooked gizzard stock (333 Cal/100 g) than from cooked chicken stock (315 Cal/100 g). Based on the existing market rates of the ingredients used and input energy requirements, the Processing ofcooked gizzard stock was found to be cost effective (22 Cal/rupee) as compared to cooked chicken stock (17 Cal/rupee).